2012
DOI: 10.1093/nar/gks810
|View full text |Cite
|
Sign up to set email alerts
|

MutSβ and histone deacetylase complexes promote expansions of trinucleotide repeats in human cells

Abstract: Trinucleotide repeat (TNR) expansions cause at least 17 heritable neurological diseases, including Huntington’s disease. Expansions are thought to arise from abnormal processing of TNR DNA by specific trans-acting proteins. For example, the DNA repair complex MutSβ (MSH2–MSH3 heterodimer) is required in mice for on-going expansions of long, disease-causing alleles. A distinctive feature of TNR expansions is a threshold effect, a narrow range of repeat units (∼30–40 in humans) at which mutation frequency rises … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
76
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 57 publications
9
76
0
Order By: Relevance
“…Nonetheless, loss of MSH2 or MSH3 leads to a significant decrease in expansion events in mouse models of HD (Manley et al 1999; Owen et al 2005) and MD1 (van den Broek et al 2002;Foiry et al 2006). Similarly, Msh3 promotes expansions in human cells (Gannon et al 2012;Halabi et al 2012). We recently demonstrated a significant decrease in expansion of both CAG and CTG repeat tracts in Saccharomyces cerevisiae in an msh3D background (Kantartzis et al 2012).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Nonetheless, loss of MSH2 or MSH3 leads to a significant decrease in expansion events in mouse models of HD (Manley et al 1999; Owen et al 2005) and MD1 (van den Broek et al 2002;Foiry et al 2006). Similarly, Msh3 promotes expansions in human cells (Gannon et al 2012;Halabi et al 2012). We recently demonstrated a significant decrease in expansion of both CAG and CTG repeat tracts in Saccharomyces cerevisiae in an msh3D background (Kantartzis et al 2012).…”
mentioning
confidence: 74%
“…However, through a mechanism(s) that remains unclear, a TNR tract can expand, increasing the number of repeats within the tract. Initially, this brings the tract into a threshold-length range (Gannon et al 2012;Concannon and Lahue 2014) (Figure 1 and Figure 2), in which these somewhat longer tracts are not pathogenic but are increasingly susceptible to expansion; individuals with this phenomenon are carriers for disease. Once a tract has expanded sufficiently, it crosses a threshold; tracts above this threshold (which is disease specific) are pathogenic and cause disease ( Figure 1).…”
mentioning
confidence: 99%
“…Chromatin structures of DNA in these two eukaryotic cell types share similarities as well as differences, and could certainly be one of the factors involved in this discrepancy. In human cells, the HDAC3 and HDAC5 histone deacetylase complexes are involved in CAG/CTG repeat expansions, and in yeast cells the HDAC3 homologue has the same effect [30,70]. However, it was shown that chromatin organization at trinucleotide repeats embedded in a yeast natural chromosome exhibit a noncanonical structure, involving binding of Hmo1p, a high mobility group protein without obvious orthologue in the human genome [71].…”
Section: Similarities and Differences Between Mammalian And Yeast Modelsmentioning
confidence: 99%
“…More recently, it was shown that short CAG/CTG slip-out structures were efficiently repaired by human MutL and MutS complexes [27,28], and to a lesser extent by MutS [27]. In mice in which Msh2, Msh3, Pms2, Mlh1 or Mlh3 were reduced or abolished, CAG/CTG repeat expansions were decreased [29][30][31][32][33][34][35][36][37]. This is also true when Msh2 was partially or totally depleted in a mouse model for fragile X premutation [38].…”
Section: Introductionmentioning
confidence: 96%
“…These properties of trinucleotide repeats may include their ability to form higher order structures in single-stranded DNA and transcripts (Liu et al 2012). Higher order structures may play an important regulatory role in numerous cellular processes, such as DNA replication repair and at various steps of gene expression ranging from transcription to mRNA decay (Gannon et al 2012). The ZFHX3 gene, also called AT motif-binding factor 1 (ATBF1), was first described as a transcription factor that inhibits the human AFP gene expression in the liver (Sun et al 2012).…”
Section: Discussionmentioning
confidence: 99%